Representation in rehabilitation research of adults with traumatic brain injury and depression: A scoping review. (12th May 2021) - Chui, Adora; Seaton, Samantha; Kirsh, Bonnie; Dawson, Deirdre R.; Colquhoun, Heather
ABSTRACT: Objective : To determine how well comorbid depression is described, defined, and measured in the rehabilitation literature that pertains to TBI and depression. Method : Scoping review of the rehabilitation sciences literature. Six databases were searched (to October 17, 2018) using the three core concepts of TBI, depression, and rehabilitation, as was for gray literature. Two independent reviewers reviewed documents for eligibility. Results : 3737 records were reviewed and 137 documents were analyzed. Primary studies (n = 126) were most prevalent and of quantitative descriptive design (n = 102). The number of participants with TBI and comorbid depression could only be determined for 81/126 (64%) of primary studies, in which they are the minority (median of 30% of sample). Depression reporting was heterogeneous and individuals with TBI and depression were not analyzed as a subgroup in most studies (n = 68, 55%). Depression self-report instruments are commonly used (14 instruments used in 111 studies). Few studies (n = 14, 19%) have participant samples with discrete severity levels of TBI and depression. Conclusions : Better participant representation and reporting of TBI and depression variables are needed to enhance comparability across studies and improve rehabilitation outcomes